Method for recording electrical activity in the brain of immobilized adult zebrafish (2018)
Zebrafish has emerged as a useful model in neuroscience and specifically in sleep research due to various advantages over other animal models, such as their low maintenance cost and ease of genetic manipulation. However, all of the sleep studies done so far use behavioral criteria to identify and measure sleep. So far, the studies that have produced brain electrophysiology data in zebrafish have focused on epilepsy; therefore there is a necessity for zebrafish sleep electrophysiology data. In this project we fabricated electrodes and developed a method of maintaining the fish immobilized outside of the water to be able to record spontaneous electrical brain activity of paralyzed adult zebrafish, and we were able to identify spontaneous sleep activity from recorded signals. We were able to record spontaneous brain activity with minimal electrical noise, and we found a significant difference in in the magnitude of the frequencies in delta range (0.5 to 4 Hz) between sections visually identified as sleep and vigilance based on time frequency analysis.